Analisis Sinkronisasi RPD 2023-2026 dan Renstra 2023-2026 dalam Upaya Peningkatan Pelayanan Publik pada Dinas Pariwisata dan Ekonomi Kreatf Provinsi DKI Jakarta - Setyawan, Ika Heru; Tjenreng, M.B. Zubahrum (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study analyzes the synchronization between the Regional Development Plan (RPD) 2023-2026 and the Strategic Plan (Renstra) 2023-2026 of the Tourism and Creative Economy Agency of DKI Jakarta Province. The purpose of this synchronization is to ensure alignment of vision, mission, goals, strategies, and policies to support the development of the tourism and creative economy sectors. A qualitative descriptive approach was used, employing methods such as interviews, observations, and document analysis. The results show alignment between the RPD and Renstra in setting priorities, such as strengthening digital-based creative economy, revitalizing leading tourist destinations, and enhancing human resource competencies. However, differences were found in implementation levels and resource allocation, with the RPD being more holistic and flexible, while the Renstra is more focused and structured. This study highlights the importance of synchronization to enhance budget efficiency, program integration, and performance accountability, which can support sustainable development in DKI Jakarta